2017
DOI: 10.1002/ldr.2842
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of a heavy metals contaminated soil using mycorrhized and non‐mycorrhizedHelichrysum italicum(Roth) Don

Abstract: Four hundred hectares of the inland and hilly part of Apulia Region (Southern Italy) were contaminated by using low-quality composts for many years. That territory now belongs to a national park and needs a sustainable soil restoration. Therefore, a greenhouse experiment was carried out to test the phytoremediation potential of the frugal Helichrysum italicum (Roth) Don, alone and mycorrhized by Septoglomus viscosum. The aims of the research were (a) to test if the H. italicum can reduce the soil content of Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…Similar behavior was observed also on other species of the genus Helichrysum , like H. italicum (Roth) G.Don subsp. italicum (Brunetti et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behavior was observed also on other species of the genus Helichrysum , like H. italicum (Roth) G.Don subsp. italicum (Brunetti et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…viscosa (Lai et al 2015;Jiménez et al 2021) showed TF higher than H. tyrrhenicum. Otherwise, in the study of Brunetti et al (2017), H. italicum subsp. italicum have shown the capability to accumulate metals mainly into roots.…”
Section: Phytoremediation Potentialmentioning
confidence: 99%
“…As can be seen in Table 1, Brunetti et al [127] have conducted a comparative study between the phytoremediation potential of frugal Helichrysum italicum and mycorrhized Helichrysum italicum by Septoglomus viscosum applied for remediation of a land contaminated by Cd, Cu, Zn, Pb, Cr, Ni, and Co, over a twelve-month period. Results showed that the non-mycorrhized plant, i.e.…”
Section: Soil Remediation and Phytoextraction Of Hmsmentioning
confidence: 99%
“…Helichrysum italicum accumulated greater amounts of HMs, especially Cr, Cu, Pb, and Zn, in their root system. On the other hand, Septoglomus viscosum used in the mycorrhized H. italicum study resulted in a better growth of plant in contaminated soils −likely because of the better soil fertility parameters in the brownfields−, however, its use decreased the uptake of HMs by the roots, which was possibly resulted from an exclusion mechanism, thereby reducing the phytoremediation capability of H. italicum and less extraction of the HMs from the contaminated soil (see Table 1) [127]. Kocoń and Jurga [111] studied a three-year micro-plot experiment to investigate the growth possibility and phytoextraction potential of two energy crops, i.e.…”
Section: Soil Remediation and Phytoextraction Of Hmsmentioning
confidence: 99%
“…We did not, however, explore the contaminative mechanism, which will be investigated in our future research. In particular, HMs are likely to react to co-contaminations with other hazardous material in soil, like polycyclic aromatic hydrocarbon (PAH) (Brunetti et al, 2018;Deary, Ekumankama, & Cummings, 2018;Wang et al, 2019). In our future research, we will study whether the proposed indices are still effective when the rice is subject to co-contaminations of Cd-Pb and PAH, and investigate how HMs harm tissues and affect photosynthesis in cell scale with hyperspectral remote sensing.…”
Section: Potential Applications and Limitationsmentioning
confidence: 99%